Sugarcane bagasse as an alternative medium for removal of hexavalent chromium from aqueous solution / I. Naimah …[et al.] - I, Naimah; H, Masitah; M.Z.M, Salwa; A.G, Azlinda; R, Nazerry Rosmady (2008)
Perlis has long been known to have the largest plantation of sugar cane in Malaysia for sugar production. The production of sugar, however, produced enormous quantity of unwanted bagasse. This by product of sugar production will be used as an alternative medium for adsorption of toxic heavy metals from industrial wastewater. The bagasse was initially modified by simple acid treatment to improve its adsorptive capacity. In order to determine its effectiveness, a study of the adsorption mechanism was conducted on the removal of 50-300 mg/L range of haxavalent chromium from aqueous solution at 30, 40 and 50°C.